In the mean time : temporal colonization and the Mexican American literary tradition - Murrah-Mandril, Erin (Postwestern horizons., 2020)
"Taking a cue from Latina/o and borderlands spatial theories, "In the Mean Time" argues that time, like space, is a socially constructed, ideologically charged medium of power in the Southwest"--